2019
DOI: 10.1080/17530350.2019.1643392
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the role of collaboration in the process of museum innovation

Abstract: The user has requested enhancement of the downloaded file.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 35 publications
(35 reference statements)
0
4
0
2
Order By: Relevance
“…En suma, este trabajo contribuye con evidencia empírica al reconocer el valor que las tIC y su impacto tienen en diversos aspectos de los museos, que van desde cuestiones de servicio, hasta aquellos de atractividad y de promoción turística (Ekuobase & Olutayo, 2016;García-Madariaga et al, 2018;García et al, 2020;Braña & Casado-Neira, 2013;Romanelli, 2018;Sun & Grimes, 2016). Las aportaciones de Amit y Zott (2001) sobre creación de valor fueron útiles para explicar cómo las tIC -desde su eficiencia, complementariedad, retención y novedad-pueden ser de gran beneficio en los espacios encargados de resguardar el patrimonio cultural, al mismo tiempo que para darlos a conocer a usuarios caracterizados por utilizar tecnologías y medios digitales en su cotidianidad, así como en actividades de tiempo libre y ocio (Gombault et al, 2016;Lee et al, 2020;Li & Coll-Serrano, 2019).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…En suma, este trabajo contribuye con evidencia empírica al reconocer el valor que las tIC y su impacto tienen en diversos aspectos de los museos, que van desde cuestiones de servicio, hasta aquellos de atractividad y de promoción turística (Ekuobase & Olutayo, 2016;García-Madariaga et al, 2018;García et al, 2020;Braña & Casado-Neira, 2013;Romanelli, 2018;Sun & Grimes, 2016). Las aportaciones de Amit y Zott (2001) sobre creación de valor fueron útiles para explicar cómo las tIC -desde su eficiencia, complementariedad, retención y novedad-pueden ser de gran beneficio en los espacios encargados de resguardar el patrimonio cultural, al mismo tiempo que para darlos a conocer a usuarios caracterizados por utilizar tecnologías y medios digitales en su cotidianidad, así como en actividades de tiempo libre y ocio (Gombault et al, 2016;Lee et al, 2020;Li & Coll-Serrano, 2019).…”
Section: Discussionunclassified
“…En las tIC, su valor se ve favorecido cuando estas se perciben como vanguardistas o novedosas por parte de los usuarios (Labanauskaitė et al, 2020). Además, el valor de las tIC está asociado con las nuevas experiencias generadas, entre ellas, las que emanan de los procesos de aprendizaje e interacción (Lee et al, 2020;Li & Coll-Serrano, 2019;Puiggrós et al, 2017;Urquhart, 2019).…”
Section: Valor De Las Tecnologías De La Información Y La Comunicación...unclassified
“…Several empirical studies have shown that cross-organizational collaboration can help to adopt external technologies and innovation in the early music industries (Castro-Martínez, Recasens, & Jiménez-Sáez, 2013), museums (Camarero et al, 2011;Vicente et al, 2012), and heritage restoration organizations (De-Miguel-molina et al, 2013;Verbano et al, 2008). Besides, Li and Coll-Serrano (2019) have explored the potential relationship between collaborative arrangements and innovation in Spanish museums, concluding that different types of collaborators play different roles in innovation outcome in terms of the type of innovation.…”
Section: Meso-level Factorsmentioning
confidence: 99%
“…To define these innovation types, we utilized the knowledge-led taxonomy based on the predominant knowledge base on which the innovative activities are grounded (Li & Ghirardi, 2019;Li & Coll-Serrano, 2019); namely, technological innovation is mostly based on an analytical and synthetic knowledge base, cultural innovation on a symbolic knowledge base, and organizational innovation on a managerial knowledge base; and different knowledge bases are primarily reflected in different disciplines in which museum staff are trained (Li & Coll-Serrano, 2019;Li & Ghirardi, 2019).…”
Section: Cultural Technological and Organizational Innovation In Museumsmentioning
confidence: 99%
“…Such attention has mostly followed two main trends in recent years. First, mainstream studies on innovation have been expanded from the technological to the cultural sphere [4], and use and functional values are no longer the sole determinant factor of value creation in the development of new products and services, whilst aesthetics, symbols and meaning also add value owing to their 'communication' component [5]. Second, design thinking, as well as design methods and tools, have been extensively developed and diffused in the last decades [6]; now it is acknowledged that design is not only valuable in addressing a wide range of managerial issues but is also a powerful tool that can be applied to problem-solving and product development beyond the creative industries [7].…”
Section: Introductionmentioning
confidence: 99%